2005
DOI: 10.1097/00001813-200511000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CK2 for cancer therapy

Abstract: Protein kinase CK2 is a highly ubiquitous and conserved protein serine/threonine kinase that has been found to be involved not only in cell growth and proliferation, but also in suppression of apoptosis. CK2 is capable of dynamic intracellular shuttling in response to a variety of signals. It is localized in both the nucleus and cytoplasm in normal cells, but is particularly predominant in the nuclear compartment in cancer cells. CK2 has been found to be uniformly dysregulated in all the cancers that have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
106
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(117 citation statements)
references
References 45 publications
10
106
1
Order By: Relevance
“…CK2 is a major player in intracellular signaling and has been implicated in the regulation of manifold cellular processes, including proliferation, differentiation, apoptosis and neoplastic transformation [43,58,59]. Although more than 300 substrates of CK2 have been identified to date, little is known about the spatiotemporal substrate specificity of the different holoenzyme complexes, which contain various combinations of two individual catalytic subunits derived from the respective a, a 0 and a 00 isoforms, and a dimer of two non-catalytic, presumably regulatory b subunits [42,59,60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CK2 is a major player in intracellular signaling and has been implicated in the regulation of manifold cellular processes, including proliferation, differentiation, apoptosis and neoplastic transformation [43,58,59]. Although more than 300 substrates of CK2 have been identified to date, little is known about the spatiotemporal substrate specificity of the different holoenzyme complexes, which contain various combinations of two individual catalytic subunits derived from the respective a, a 0 and a 00 isoforms, and a dimer of two non-catalytic, presumably regulatory b subunits [42,59,60].…”
Section: Discussionmentioning
confidence: 99%
“…The further dissection of this mechanism subsequently revealed that the HuR protein ligand APRIL (ANP32B) acts as an adaptor that connects the HuR-bound CD83 transcript with the CRM1 export receptor [35]. The further finding that phosphorylation of Thr 244 in APRIL regulates its nuclear export [35] finally provided the framework of this study, which was aimed at the identification of the Thr 244 -specific kinase and its functional analysis with respect to CD83 expression.We here identified CK2 as the Thr 244 -specific APRIL protein kinase and demonstrated that inhibition of CK2 interferes with CD83 expression primarily by impairing the cytoplasmic accumulation of CD83 mRNA.CK2 is a major player in intracellular signaling and has been implicated in the regulation of manifold cellular processes, including proliferation, differentiation, apoptosis and neoplastic transformation [43,58,59]. Although more than 300 substrates of CK2 have been identified to date, little is known about the spatiotemporal substrate specificity of the different holoenzyme complexes, which contain various combinations of two individual catalytic subunits derived from the respective a, a 0 and a 00 isoforms, and a dimer of two non-catalytic, presumably regulatory b subunits [42,59,60].…”
mentioning
confidence: 98%
“…The induction of apoptosis in vivo by intratumoral administration of antisense CK2 , or a peptide that impairs phosphorylation by CK2 (Perea et al, 2004), has provided the proof of principle evidence for potential targeting of CK2 to produce cell death in vivo. Subsequently, we also originally reported that CK2 can be targeted by antisense CK2 delivered via the systemic route into the animal such that apoptotic response in tumor xenograft cells was observed in vivo (Ahmad et al, 2005). These observations have paved the way towards devising potential approaches to cancer therapy by targeting CK2 Ahmad et al, 2005).…”
Section: Ck2 and Cell Deathmentioning
confidence: 97%
“…Subsequently, we also originally reported that CK2 can be targeted by antisense CK2 delivered via the systemic route into the animal such that apoptotic response in tumor xenograft cells was observed in vivo (Ahmad et al, 2005). These observations have paved the way towards devising potential approaches to cancer therapy by targeting CK2 Ahmad et al, 2005). It is noteworthy that chemopreventive dietary agents such as resveratrol and EGCG (epigallocatechin-3-gallate) which are known to have mild apoptotic activity in cancer cells appear to mediate this effect at least in part via targeting of CK2, raising the possibility of employing these polyphenolic compounds alongside suboptimal levels of inhibitors of CK2 in combination chemotherapy (Ahmad et al, 2007).…”
Section: Ck2 and Cell Deathmentioning
confidence: 99%
“…At present, we do not know if this catalytic form of CK2 is actually present as a monomer, or rather combined in other molecular complexes; it will be also important to search for protein substrates eventually phosphorylated in R-CEM by CK2a, but not by a 2 b 2 . What we can say is that CK2, recently proposed as an oncogenic target (Ahmad et al, 2005;Seeber et al, 2005), should be taken into special consideration whenever the tumor displays drug resistance, given the ability of CK2 inhibitors to revert the MDR phenotype.…”
Section: Implication Of Ck2 In the Mdr Phenotype Of Cem Cells G DI Mamentioning
confidence: 99%